2020
DOI: 10.21203/rs.3.rs-92836/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial Distribution and Predictors of Domestic Violence Among Women Aged 15-49 in Ethiopia: Analysis of EDHS 2016 Dataset.

Abstract: Introduction: Violence against women particularly that is commited by an intimate partner is becoming a social and public health problem across the world. Studies from different countries shows that the spatial variation in distribution of domestic violence was commonly attributed by neighborhood level predictors. Despite the importance of spatial techniques, studies that employ it in Ethiopia are limited. Therefore, the aim of this study is to determine the spatial distribution and predictors of domestic viol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…This finding showed that there is spatial variation in the distribution of IPV within South Africa. This is in line with existing evidence from Ghana [18], Uganda [19] and Ethiopia [5]. A plausible justification in support of our findings could be the pervasiveness of misconceptions about IPV and prevailing cultural beliefs that reinforce acts that fall under the category of IPV [33].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This finding showed that there is spatial variation in the distribution of IPV within South Africa. This is in line with existing evidence from Ghana [18], Uganda [19] and Ethiopia [5]. A plausible justification in support of our findings could be the pervasiveness of misconceptions about IPV and prevailing cultural beliefs that reinforce acts that fall under the category of IPV [33].…”
Section: Discussionsupporting
confidence: 91%
“…Evidence from the 2017 Statistics South Africa report shows that approximately one out of five adult women in South Africa had ever experienced violence by a partner [4]. Also, evidence from the 2016 South African Demographic and Health Survey (SADHS) indicates that the prevalence of IPV among women was 21.9% which is lower than the regional IPV prevalence [5]. This variation between the IPV prevalence as reported in the 2016 SADHS and the Southern Africa's IPV prevalence could be attributable to spatial variations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, The impact of violence on women's health extends to their physical, mental, sexual, and reproductive well-being, and in certain contexts, it can heighten the risk of HIV transmission [2]. Also, IPV is linked to various mental health concerns, encompassing anxiety, depression, suicidal thoughts and behaviors, as well as posttraumatic stress disorders [6].…”
Section: Introductionmentioning
confidence: 99%